Answering the Call: Virtual Migration in Indian Call Centres. (June 2014) - Carrillo Rowe, Aimee; Malhotra, Sheena; Pérez, Kimberlee
<x content-type="archive" xml:space="preserve">Abstract</x> This paper explores the daily, psychic journeys Indian call center agents undergo as they 'virtually migrate' between India and the US. A thin cable that runs half way around the globe bridges the 'here' and the 'there', connecting agents to faraway customers in real time. The new time-space relations generated by this virtual contact create conditions for these workers to undergo a global 'migration' from India and to America, even as their bodies remain bounded within the national homeland. To accommodate the US American workday, Indian agents often work the nightshift and sleep during the day, leaving them little time for family, friends, and cultural events. This temporal arrangement displaces them from the daily rhythms of Indian life, generating a sense of loss, longing, and nostalgia for 'India'. Further, while agents experience a sense of distance from India, they also experience a movement toward 'America'. Agents' accounts suggest a feeling of living between worlds, yet their movement is decoupled from physical migration.